2017
DOI: 10.1186/s40168-016-0209-7
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota fingerprints lose individually identifying features over time

Abstract: BackgroundHumans host individually unique skin microbiota, suggesting that microbiota traces transferred from skin to surfaces could serve as forensic markers analogous to fingerprints. While it is known that individuals leave identifiable microbiota traces on surfaces, it is not clear for how long these traces persist. Moreover, as skin and surface microbiota change with time, even persistent traces may lose their forensic potential as they would cease to resemble the microbiota of the person who left them. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
259
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(280 citation statements)
references
References 29 publications
19
259
2
Order By: Relevance
“…were associated with more severe disease whereas they were reduced as disease is controlled with dexamethasone (Luo et al, 2017). The microbiota of MRL/lpr mice, on the other hand, were described to be depleted of Lactobacillaceae and a mix of Lactobacillus strains improved outcomes in this lupus model (Mu et al, 2017b, 2017a; Zhang et al, 2014). These studies did not include gnotobiotic experiments or define which strain mediates the observed effects, making a causal relationship difficult to establish.…”
Section: Discussionmentioning
confidence: 95%
“…were associated with more severe disease whereas they were reduced as disease is controlled with dexamethasone (Luo et al, 2017). The microbiota of MRL/lpr mice, on the other hand, were described to be depleted of Lactobacillaceae and a mix of Lactobacillus strains improved outcomes in this lupus model (Mu et al, 2017b, 2017a; Zhang et al, 2014). These studies did not include gnotobiotic experiments or define which strain mediates the observed effects, making a causal relationship difficult to establish.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, regrowth or after growth of microorganisms in treated DW, including BW, can occur [10,[15][16][17][18]. Uncontrolled growth of bacteria, notably biofilm bacteria, in water mains and premise plumbing during delivery is well documented and can introduce operational issues within distribution systems, resulting in deterioration of color and taste or causing potential human hygiene problems [8,10,17,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Researches have demonstrated the potential to identify a single individual in large populations, based on microbial fingerprints from metagenomic tags, even over long periods of time [42,55]. It has also been shown that skin bacterial profiles can be confidently used to link specific individuals to objects touched, even after months [56], provided the objects have since remained untouched [31]. Furthermore, it is possible to define specific biogeographical patterns from different objects, based on particular microbiome signals; for instance, toilets, doorknobs and restroom floors faithfully reflect the microbiome characterizing the human gut, skin and soil bacterial profiles respectively [26].…”
Section: Identitymentioning
confidence: 99%